Louis Althusser y Judith Butler: génesis y actualidad del postestructuralismo - Castellanos, Belén (Nómadas. Critical Journal of Social and Juridical Science, 2009)
In this article we will try to shed some light on the problematic reception of Marx's work and traditional Marxism by post-structuralism. For that, we will propose Louis Althusser as the father of post-structuralism; we will fix our eyes preferrably on one of his most polemic articles, “Two or three (brutal) words about Marx and Lenin”, in which he introduces a series of problems that would be later developed in his book Marx in his limits. We would like to expose how since that work he denounces a growing attitude, in the Marxist tradition, consisting of separating, in theory and in struggle, the economic issues and the political issues, thus establishing a hierarchy of the first over the latter. Nevertheless, we are also interested in showing how this denounce does not share the structuralist scheme that essentializes the cultural issue in the symbolic order, which would restrict (castrate) any project of economic and social subversion, thus sending a message of political pessimism. After that we will read an article from Judith Butler, openly post-structuralist thinker, entitled “Merely cultural”, in which we will follow the lines opened by Althusser, and thus find him at the genesis of such a current, contributing to dismantle the myth of a structuralist Althusser.
Keywords: Post-structuralism; Crisis of Marxism; Postmodernity; Capitalism; Surplus value; Production; Reproduction; Value quantification; Class struggle; State; Legal power; Exploitation; Class; Dualism Party-trade union; Myth of self-consciousness; Material modes; Social movements; Identity; Difference